PEMODELAN PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN DAN KOTA DI JAWA TENGAH MENGGUNAKAN GEOGRAPHICALLY WEIGHTED RIDGE REGRESSION - Depy Veronica; Hasbi Yasin; Tatik Widiharih (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2016)
Linear Regression Analysis is a statistical method for modeling the relation between response variable and predictor variable. Geographically Weighted Regression (GWR) is an expansion of linear regression model if spatial heterogeneity occurred. Local multicollinearity test is required to know the presence of linear correlation between independent variables for each observation location. Geographically Weighted Ridge Regression (GWRR) is a extension of GWR model to solve local multicollinearity problem. Parameter estimation for GWR and GWRR model is done using Weighted Least Square (WLS) method by applying optimum bandwith with Cross Validation (CV) criteria. GWRR model is applied on locally generated recurring revenues (PAD) at district and city of Central Java and its result shows the ability of GWRR model to erase multicollinearity problem. Based on Mean Squared Error (MSE) and Akaike Information Criterion (AIC) value for GWR and GWRR model, it is know that the best model to analyze locally generated recurring revenues (PAD) at district and city of Central Java is GWRR model with the smallest MSE and AIC value. Keywords : Akaike Information Crietion, Spasial Heterogeneity, Geographically Weighted Ridge Regression, Mean Square Error, Local Multicoliniearity